Biomechanical factors in sprint training- where science meets coaching - Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This paper examines the biomechanics of sprinting and sprint training. Various biomechanical models of sprint performance are considered with respect to the start, acceleration and speed maintenance phases of the 100 m sprint event together with the research that underpins those models. The impact of research on strength and conditioning training is discussed with special reference to the control of leg-spring stiffness and the applications of resistance and complex training modalities. Training practises for sprinting are discussed with respect to scientific evidence. The relevance of commonly used sprint and running drills is evaluated in relation to the kinematics and muscle activation patterns in sprinting. Finally, a simple coaching related model for the development of sprinting is presented which is consistent with scientific evidence.